2018
DOI: 10.1021/acs.est.8b04481
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the Deployment of Anaerobic Digestion to Meet Zero Waste Goals

Abstract: The U.S. places approximately 53% of its total municipal solid waste (MSW) in landfills, but state and local governments across the country are now setting ambitious environmental and waste diversion policies requiring, among other things, diversion and utilization of organics. Municipalities across the U.S. are employing anaerobic digestion (AD) as part of their strategy to divert organic MSW from landfills, produce biogas, and yield other beneficial coproducts such as compost and fertilizer. However, AD face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 28 publications
(41 reference statements)
0
49
0
Order By: Relevance
“…3, the biogas yield was 6 L L −1 after 3 days of anaerobic digestion. However, due to the short microorganism activity time, there was much uncertainty in their growth, and they were easily affected by microbes in the MSW aerobic sludge 26 . In brief, the experimental results showed that grinding CFR to about 5 cm in diameter was sufficient when the retention time of anaerobic methylation was more than 15 days.…”
Section: Resultsmentioning
confidence: 99%
“…3, the biogas yield was 6 L L −1 after 3 days of anaerobic digestion. However, due to the short microorganism activity time, there was much uncertainty in their growth, and they were easily affected by microbes in the MSW aerobic sludge 26 . In brief, the experimental results showed that grinding CFR to about 5 cm in diameter was sufficient when the retention time of anaerobic methylation was more than 15 days.…”
Section: Resultsmentioning
confidence: 99%
“…increase global SOC stocks by 0.4%, can benefit from strategic regional management and application of organic waste streams as this can lead to widespread carbon sequestration. 41 Unlike California, regions with limited farmland in close proximity to cities may have less success in implementing this strategy. The CAN model can play a key role in helping governments quantify the potential of large-scale nutrient cycling systems by predicting the amount of compost that can be allocated to farmland, the area of farmland that can be supplied compost, and the amount of GHG reductions associated with the system.…”
mentioning
confidence: 99%
“…Anaerobic digesters have an important role to play in diverting organic waste from landfills and producing renewable energy. 5 AcoD technology in particular is being embraced as a pragmatic strategy for increasing biogas production, leveraging existing infrastructure, while overcoming the challenges associated with the substrate properties and system stability in singlesubstrate AD process. The key to the success of AcoD processes is system optimization, and an ability to manage a diverse set of incoming waste streams.…”
Section: <Figure 6>mentioning
confidence: 99%
“…[1][2][3] Ambitious "zero waste" policies from local and state governments across the U.S. will require substantial new investments in infrastructure to divert organic waste from landfills, and AD is an essential part of any viable strategy. 4,5 However, developing predictive modeling capabilities to estimate biogas yield and composition as a function of feedstock types has proved challenging. Unlike industrial bioreactors where a single microbial host utilizes a pure substrate (e.g.…”
Section: Introductionmentioning
confidence: 99%